2021
DOI: 10.1292/jvms.21-0038
|View full text |Cite
|
Sign up to set email alerts
|

<i>Toxoplasma gondii</i> antibody prevalence and isolation in free-ranging cats in Okinawa, Japan

Abstract: Cats are an important host of Toxoplasma gondii from an epidemiological perspective because they are the only definitive hosts that excrete oocysts in their feces. In this study, 201 free-ranging cats in Okinawa were examined for T. gondii infection. Using the latex agglutination test, we detected antibodies against T. gondii in 26.9% (54/201) of the cats. Oocysts of T. gondii were not detected upon microscopic examination of the feces of 128 cats. T. gondii was isolated from the tissues of 9 out of 24 seropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The present study revealed the circulation of the type-I GRA6 allele in fecal samples of domestic cats in Phayao, Thailand. This result was consistent with the detection of type-I T. gondii GRA6 in domestic cats in South Thailand [46] and Okinawa, Japan [47]. Other studies have considered type-II T. gondii as the predominant genotype for feline definitive hosts in China [44] and stray cats in Iran [48].…”
Section: Discussionsupporting
confidence: 88%
“…The present study revealed the circulation of the type-I GRA6 allele in fecal samples of domestic cats in Phayao, Thailand. This result was consistent with the detection of type-I T. gondii GRA6 in domestic cats in South Thailand [46] and Okinawa, Japan [47]. Other studies have considered type-II T. gondii as the predominant genotype for feline definitive hosts in China [44] and stray cats in Iran [48].…”
Section: Discussionsupporting
confidence: 88%
“…The infection rates in some parts of Africa and Europe are higher than the world average infection level, such as a 97.4% positive serological test for T. gondii in wild cats in Egypt (Dubey 2010), 62.3% in Albanian cats (Spada et al 2012), 70.9% in Algeria cats (Ouchetati et al 2021), 40.3%-76% in Turkish cats (Dubey 2010;Can et al 2014), 48.4% in Finnish cats (Jokelainen et al 2012), 42.4% in Switzerland (Schreiber et al 2021, 51.6% in Latvia (Deksne et al 2013), 58.95% in France (Afonso et al 2013), 60.8% in Estonia (Must et al 2015), 32.3% in Cyprus (Attipa et al 2021) and 24.2 to 60% in Spain (Montoya et al 2018;Candela et al 2022). The prevalence rates of T. gondii infection in cats in most of Asia are generally lower than the world average, such as 19.6% in Kuwait (Abdou et al 2013), 30.4% in Iraq (Switzer et al 2013), 24.5% in China (Ding et al 2017;Li et al 2022), 2.2 to 47.2% in Korea (Hong et al 2013;Jung et al 2017), 4.8 to 11% in Bangkok (Jittapalapong et al 2010Sukhumavasi et al 2012), 40% in Iran (Sharif et al 2009), 14.5% in Malaysia (Wana et al 2020), 9 to 26.7% in Japan (Matsuu et al 2017;Kyan et al 2021) and18.7% in Thailand (Huertas-López et al 2021). For countries in Americas, the prevalence rates were 8 to 84.4% in Brazil (Cavalcante et al 2006;Bastos et al 2014;Magalhães et al 2017;Lima et al 2018), and 6 to 66.7% in the United States (Lilly et al 2013;Ballash et al 2015;Scorza and Lappin 2017).…”
Section: Catmentioning
confidence: 97%
“…In addition, 24 strains were successively isolated in Okinawa, a southern part of Japan, (Supplementary Fig. S1 ), between 2008–2013 18 , 19 . An atypical strain TgCatJpGi1/TaJ which was isolated in central Honshu, the main island of Japan (Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%